Make green growth a priority: issues and challenges in organising green sports tourism events - Lim, Khong Chiu; Ramely, Asmahany; Abdul Wafi, Anisah (2019)
Despite many sports tourism events have been organized globally yet the understanding about the event greening practices are reasonably low, hence the impacts of the sports event towards the environment and the communities are exceptionally high. The green concept imp1ementation into sports based events is important because it will increase the awareness among the people, organizers, participants, and spectators about the occurrence. This conceptual paper focuses on the'issue of conceptualization and implementation of green sports events which covering on the theory and principles of green practices, strategies and in~plementationo f green practices in the case of the selected Olympic Games, issues and challenges, and the roles of stakeholders for effective implementation of greener sports events. As such, the green sports events have a great potential to reduce the negative impacts of the sports events to the environment and the community at large. Furthermore, it's also assist the organizers and participants cultivate awareness through environmentally friendly strategies in organising sports events. In addition, this paper also provides with some "green" suggestions to be considered by sports event organisers.